Physicochemical characteristics and microbiological quality of silkworm (Bombyx mori) larval and pupae powder : comparative study - Loo, Yuet Ying; Lim, Hui Ying; Noor-Soffalina Sofian-Seng,; Wan Aida Wan Mustapha,; Noorul Syuhada Mohd Razali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Silkworm (Bombyx mori) has been reported to exhibit diverse health benefits. A comparative study was conducted to evaluate the physicochemical (colour, water activity, pH, water solubility, proximate, mineral, amino acid, and fatty acid composition) and microbiological qualities of Bombyx mori silkworm powder produced from two developmental stages (larvae and pupae). Silkworm pupae powder (SPP) had significantly higher (p<0.05) lightness (L*) and yellowness (b*) values than silkworm larval powder (SLP). SPP had significantly higher (p<0.05) water activity and solubility than SLP. The pH values of both silkworm powders were not statistically different. SLP had significantly higher (p<0.05) protein and moisture but significantly lower (p<0.05) fat, ash, fibre, and total calorie content as compared to SPP. The total amino acid content of SPP was significantly higher (p<0.05) than SLP. SLP had significantly higher (p<0.05) protein efficiency ratio than SPP, indicating that SLP contained higher amount of essential amino acid. Both silkworm powder contained 20 types of fatty acids with SPP exhibited significantly higher (p<0.05) polyunsaturated fatty acid composition than SLP. Both silkworm powders had a low n-6/n-3 ratio, which may be beneficial to human health. Both SLP and SPP could be a good source of iron and rich in magnesium and zinc. SPP had a significantly lower (p<0.05) yeast and mould count as compared to SLP. The finding of this study suggested that silkworm powder produced from two different developmental stages may provide beneficial health effects in humans derived from the protein, minerals, fatty acids, and amino acids content.